2014
DOI: 10.1038/bmt.2014.102
|View full text |Cite
|
Sign up to set email alerts
|

Similar survival, but better quality of life after myeloablative transplantation using unrelated cord blood vs matched sibling donors in adults with hematologic malignancies

Abstract: This study included data from 185 consecutively treated patients, 16 years of age or older, who underwent myeloablative transplantation using unrelated umbilical cord blood (UCB) (UCB transplantation (UCBT), n = 70) or HLA-identical sibling donor peripheral blood stem cells alone or combined with bone marrow (BMT/PBSCT, n = 115) from October 2001 to December 2012. All patients received myeloablative regimens, cyclosporin A plus mycophenolate mofetil as prophylaxis for GVHD, and similar supportive care. Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 34 publications
2
9
1
Order By: Relevance
“…In addition, several recent studies demonstrated highly similar survival results between CBT and MSD recipients [12][13][14]27,45,46]. However, in this study, the rate of OS after CBT was significantly inferior to that after BMT or PBSCT from MSDs.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…In addition, several recent studies demonstrated highly similar survival results between CBT and MSD recipients [12][13][14]27,45,46]. However, in this study, the rate of OS after CBT was significantly inferior to that after BMT or PBSCT from MSDs.…”
Section: Discussioncontrasting
confidence: 52%
“…Since the lower incidence of severe GVHD is one of the advantages of CBT [8,10,11,26,27], the higher incidence of GVHD using older MSDs could be overcome using CB for older patients. In addition, the absence of risk to donors may also be advantageous with CBT because the risk of adverse events during donation increases with the age of the donor [26].…”
mentioning
confidence: 99%
“…Furthermore, our previous study showed that long-term survivors with CBT had less cGVHD and higher quality of life compared to HCT in HLA-identical sibling's donors. 47 Thus, our protocol of MMAC without ATG not only makes full use of the GVL effects of CBT but also keeps its advantage of low probability of cGVHD.…”
Section: Cancer Therapy and Preventionmentioning
confidence: 99%
“…New strategies should be further investigated to improve the antileukemic effect after CBT. We have reported that myeloablative CBT can result in improved survival and decreased relapse rates in adult or pediatric recipients with hematologic malignancies 3,4 compared with transplants from HLA-matched sibling donors (MSD); however, few studies have presented a comparative analysis of myeloablative CBT and allo-HCT from MSD for AML in a disease-specific manner. GvHD-free and relapse-free survival (GRFS) is a novel composite end point of allo-HCT, and takes into account severe acute GvHD (aGvHD), extensive chronic GvHD (cGvHD), TRM and relapse, and represents real recovery after allo-HCT.…”
Section: Introductionmentioning
confidence: 99%